2018
DOI: 10.3390/foods8010004
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the Probiotic Lactobacillus Plantarum ATCC 14917 Strain to Produce Functional Fermented Pomegranate Juice

Abstract: In this research survey the application of probiotic strain Lactobacillus plantarum ATCC 14917 in pomegranate juice fermentation is sought. Pomegranate juice was fermented for 24 h and then it was stored 4 for 4 weeks. Cell viability retained in high levels after the 24 h of fermentation and storage for 4 weeks (above 8.8 log cfu/mL), while fermented pomegranate juice was scored better at the 4th week of storage compared to non-fermented pomegranate juice. The probiotic strain was effective regarding l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 61 publications
7
70
0
1
Order By: Relevance
“…Regarding the viability of probiotic strain used in this study, the various beverages were checked for its viable numbers of L. plantarum using MRS media (Biolife Italiana, Milano, Italy) according to Mantzourani et al (2019).…”
Section: Viable Counts Of L Plantarummentioning
confidence: 99%
“…Regarding the viability of probiotic strain used in this study, the various beverages were checked for its viable numbers of L. plantarum using MRS media (Biolife Italiana, Milano, Italy) according to Mantzourani et al (2019).…”
Section: Viable Counts Of L Plantarummentioning
confidence: 99%
“…Results of the study showed that Lactobacillus plantarum ATCC 14917 was remained viable during the whole cold storage period and no significant sensory differences were observed among the fermented and the non-fermented samples. Also in another study by the same group [63], showed that the same probiotic strain can be used for the fermentation of pomegranate juice. Reference [41] used as a substrate apricot juice for the production of a novel non-dairy probiotic beverage.…”
Section: Fruits and Vegetablesmentioning
confidence: 93%
“…Pomegranate juice fermented with probiotic L. plantarum ATCC 14,917 showed a higher total phenolic level and higher antioxidant activity [130]. In a study, Shalgam juice, which contains phenolic and microbial compounds, prevented the growth of Caco-2 cell lines [131].…”
Section: Non-dairy In Vitro Blueberry Beverages Controlled Retinal Pimentioning
confidence: 99%